(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Aquatic environment is faced with pollution problems most of which are anthropogenic in nature. Feroro stream water was evaluated for its quality and suitability for the growth of organisms. The temporal and spatial qualities of the water was observed to be deteriorating. Water sampling was done once monthly for twenty-four months from five stations along the stream. The water samples were put into 2-litre sterilized plastic bottles. Some physical and chemical parameters were determined using HANNA meter, Dissolved oxygen meter, titration and colorimeter methods. All the parameters tested ranged within Federal Ministry of Environment standard limits. Turbidity and Total Hardness are above the standard limits. There was significant difference temporally P<0.05. Electrical Conductivity was significant different in all the stations P<0.05, lowest at Station 1(137.55µS/cm) and high at Station 5 (235.21µS/cm). Across the wet and dry seasons, the parameters significantly varied except in Temperature (25.79±0.12 and 25.57±0.26) and Total Hardness (119.68±6.13 and 109.50±3.38) P<0.05.